A 1-Year Accredited Nurse Residency Program's Effect on Intent to Leave. (December 2021) - Failla, Kim Reina; Ecoff, Laurie; Stichler, Jaynelle F.; Pelletier, Luc R.
Abstract : OBJECTIVE: This article describes the evaluation of a system-wide program to enhance new graduate nurse resident (NGNR) experience, enculturation, and commitment to the organization. BACKGROUND: Structured nurse residency programs support NGNR transition to the work environment and increase retention and organizational commitment. METHODS: The study used a descriptive, comparative design measuring NGNR perceptions of affective commitment, job satisfaction, job stress, and other variables over 3 times from baseline to 24 months. RESULTS: Findings demonstrated a reduction in affective commitment and an increase in nursing stress from baseline to 12 and 24 months of employment. The highest mean in intent to leave occurred at 12 months, highlighting the vulnerability of the NGNR at that time. CONCLUSIONS: Nurse leaders must consider resources supporting NGNRs beyond the traditional 12 months to ensure retention and organizational commitment, thereby decreasing intent to leave.